Comparing the Effectiveness of Case Based Learning with Conventional Teaching in Anatomy - Shema K Nair; Neha Rai (Academia Anatomica International, 2019)
Introduction: Case based learning (CBL ) is an efficient method of making dry subject like anatomy interesting and student centered. Subjects and Methods: A group of students of 1st MBBs were taught by CBL while the other group was taught by conventional teaching methods and both the groups were assessed for their performance. Results: Students had a better understanding of the topic on being taught by CBL. Conclusion: CBL is a good approach to teach anatomy to medical students as it makes the subject quite lively and clinically oriented.